An efficient topology reconfiguration algorithm for high speed connection-oriented LANs - Biswas, Subir Kumar (International journal of communication systems, 1997)
This paper deals with the design and performance issues of a protocol, proposed for dynamic topology reconfiguration in high‐speed connection‐oriented local area networks (LANs). A distributed reconfiguration algorithm is introduced where each network node maintains the minimum‐hop‐tree connectivity information, corresponding to all the physically reachable network interfaces within the local subnetwork. An incremental and adaptive tree‐maintenance strategy is designed for keeping a reconfiguration process isolated from the unaffected parts of the network. A call‐by‐call routing algorithm, working on top of this reconfiguration protocol, is also proposed with multiple heuristics for optimizing the end‐to‐end connection hop‐count and network load distribution. Simulation results illustrating the correctness and performance of these protocols are included in this paper. Issues regarding a prototype implementation of the presented protocols are also discussed. © 1997 John Wiley & Sons, Ltd.